The Effect of Motivational Self-Talk on Reducing Anxiety in Short-Distance and Middle-Distance Runners - Ikina Rizki Kahiji; Komarudin; Ira Purnamasari (Universitas Negeri Semarang, 2025)
The aim of this study is to examine the effect of motivational self-talk on the anxiety level of short-distance and middle-distance runners. Anxiety, as experienced by the players, particularly before competitions, can have a negative influence on their performance. Motivational self-talk is a psychological intervention technique used to enhance concentration, build self-confidence, and reduce competitive anxiety. The design of the study utilized in this case was a one-group pretest-posttest quasi-experimental study. The sample consisted of 29 athletes from Sekolah Atletik Pajajaran Bandung, who were short-distance and middle-distance runners. Anxiety was quantified using the Sport Anxiety Scale-2 (SAS-2). Treatment was a motivational self-talk training package that was presented in 12 sessions and included the skills of countering, reframing, and affirming. Paired sample t-test of the data showed that motivational self-talk reduced the anxiety level of short-distance (p < 0.05) and middle-distance runners (p < 0.05). The results of the independent sample t-test showed no significant difference between the two groups (p > 0.05), which meant that motivational self-talk affected both of them equally. The study concludes that motivational self-talk reduces anxiety in short- and middle-distance runners and is recommended to be included in general athlete training programs.